#TITLE_ALTERNATIVE# - KAROSEKALI (NIM 15106048); Pembimbing: Dr. Ir. Eka Djunarsjah, MT., dan Ir. Catur Purwanto, HERIANTO
The activities sea pipeline installation is requiring information about the state of the seabed that will be passed in pipelines. The condition of the sea bed knows from marine surveys. Magnometer is one of technology that used in marine survey. Survey of magnometer is used to detect the seabed metal objects which may be dangerous in process of installation. It may cause from the shipwrecked, pipes, cables, and other hazard which is found in the survey of the laying pipe areas. The main purpose of this magnometer survey is to obtain the value of the field in magnetic intensive anomaly which is indicating the character of metal objects in the survey area. Intensity anomaly of the magnetic field is generated by the local magnetic field which is corrected with daily and IGRF corrections. Daily correction is gets from measuring magnetic field based on the stations and IGRF model which has been determined. The product of anomaly survey is a map of magnetic intensive anomaly. It is show the position of the metal object in the survey area, especially in the subsea of pipeline.